UJI PEMBERIAN PUPUK HAYATI BIOTAMAX DAN EKSTRAK TEH TERHADAP PERTUMBUHAN DAN HASIL KANGKUNG DARAT ( Ipomoea reptans, Poir.) - Sri Hardiatmi & Endang Sri Sudalmi (Joglo, 2016)
The aim of this research was to figure out the following things; (1) The effects of Biotamax organic fertilizer on the growth and yield of kangkung, (2) The effects of tea extract on the growth and yield of kangkung, (3) The interaction between Biotamax organic fertilizer and tea extract on the growth and yield of kangkung. This research used Complete Randomized Design (CRD) which arranged factorially. They Randomized consist of 2 treatment factors; Biotamax organic fertilizer and tea extract, each combination treatment was repeated 5 times. The data from this research was analized by using various analisis continues by BNJ test in the level 0f 5%. The result showed that (1) the giving of Biotamax organic fertilizer can increase the number of leaves on each plant and the weight of edible portion. How ever this analyzis is not really significant when it is compared to those which is not given the Biotamax organic fertilizer.( 2 ) The giving of tea extract with 15 g/l concentrate can increase the number of leaves on each plant and the weight of edible portion. It is not real when it is compared to those which is not given the tea extract with the level of 5g/l concentrate and 10g/l concentrate. (3). The interaction between Biotamax organic fertilizer and tea extract really affect to the height of the plant, bruto weight of the plant, and dry weight of the plant after 40 days of planting. The real interaction affect for the hight of the plant gained in the level of 5 g/l tea extract giving, while for the net weight and the dry weight gained in the giving of biotamaz organic fertilizer and the level of 5g/l tea extract giving; and the giving of 10 g/l of tea extract without biotamax.Key words: Organic fertilizer, tea extract, water spinach